2000
DOI: 10.1046/j.1524-4725.2000.99288.x
|View full text |Cite
|
Sign up to set email alerts
|

Injectability and Tissue Compatibility of Poly-(N-Vinyl-2-Pyrrolidone) in the Skin of Rats: A Pilot Study

Abstract: Poly-(N-vinyl-2-pyrrolidone) is easy to inject intracutaneously and is well tolerated in the rat model. Short-term volume retention is good. Histopathology suggests a subclinical inflammatory reaction expected with implantation of a synthetic substance into the skin. Additional studies are necessary to investigate the continued persistence of the hydrogel and its long-term effects on surrounding tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[20][21][22] Marler and colleagues used a dorsal subcutaneous injection model to compare the histo-morphometry of three forms of a calcium alginate hydrogel for 8 weeks. [20][21][22] Marler and colleagues used a dorsal subcutaneous injection model to compare the histo-morphometry of three forms of a calcium alginate hydrogel for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[20][21][22] Marler and colleagues used a dorsal subcutaneous injection model to compare the histo-morphometry of three forms of a calcium alginate hydrogel for 8 weeks. [20][21][22] Marler and colleagues used a dorsal subcutaneous injection model to compare the histo-morphometry of three forms of a calcium alginate hydrogel for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Marler and colleagues used a dorsal subcutaneous injection model to compare the histo-morphometry of three forms of a calcium alginate hydrogel for 8 weeks. 21 Fernandez-Cossio studied the biocompatibility of a HA filler (Perlane) and polyacrylamide gel filler (Aquamid) at four time points in an 8-month study, 22 but only Marler and colleagues reported assessment of volume change over time as an outcome measure. 21 Fernandez-Cossio studied the biocompatibility of a HA filler (Perlane) and polyacrylamide gel filler (Aquamid) at four time points in an 8-month study, 22 but only Marler and colleagues reported assessment of volume change over time as an outcome measure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations